Impiego strutturale dei calcestruzzi fibro rinforzati modellazioni teoriche e verifiche sperimentali - Rizzuti, Lidia; Spadea, Giuseppe; Bencardino, Francesco; Bruno, Domenico (My University, 2014)
Recently researches, in the field of civil engineering, have been addressed to study high performance concrete materials. In particular Fiber Reinforced Concrete (FRC) materials are very promising. With the addition of fibers into the concrete matrix, a brittle material like concrete can be modified towards a composite material with some ductility properties, able to absorb notable impact energy due to the dynamic or cyclic actions, like the seismic action, in the “during and post” cracking stage. Although, several studies were developed further research is needed to investigate some topics. The present work deals with the study of FRC materials used for structural applications with reference to the material and structural behaviour. Initially, the compressive and the tensile behaviour of the FRC material were analyzed by experimental, theoretical and numerical approaches. Specifically, an experimental investigation and a numerical analysis were carried out with the aim to identify the parameters like fiber types and contents, that are able to improve the performance of FRC material with reference to the structural behaviour. The implications on the use of fibers added into the concrete matrix on the workability at the fresh state and on the toughness at the hardened state were also considered. The aim of the experimental investigation was to analyze and compare the mechanical and the fracture properties of FRC materials by varying some main parameters like matrix compressive strength, fiber types (steel/polypropylene), fiber volume content (Vf) and the length of steel fibers (Lf). Through the numerical analysis it was possible to investigate the influence of high steel fiber content on the tensile post-peak behaviour. The numerical results obtained were compared with the experimental ones and the reliability of the numerical procedure was checked. A comparative study was carried out between experimental and theoretical stress-strain relationships available in literature, with particular reference to compressive behaviour of FRC. The aim was to evaluate the reliability of the proposed models and their range of validity. Several experimental data available in literature were analyzed and collected in a database. The above database was integrated with further experimental results obtained in the Laboratory of the Department of Structural Engineering at the University of Calabria. At the same time, the analytical uniaxial stress-strain relationship available in literature were analyzed and collected. Each theoretical model was critically analyzed and the reliability was checked through a comparison with the experimental curves of the same author and other available in literature. Subsequently, the structural behaviour was studied. With reference to the behaviour of eccentrically loaded FRC columns interaction diagrams axial load (N) – bending moment (M) of the cross section were computed to highlight the role of some main parameters on the strength. The theoretical models proposed in the Italian guideline CNR-DT 204 (2006) and other models available in literature were used in the analysis. The reliability of the theoretical models to describe the real behaviour of fiber reinforced concrete elements was checked through a comparison with some experimental data on steel fiber reinforced concrete columns subjected to eccentric loads available in literature. With reference to a rectangular FRC cross section, symmetrically reinforced, interactions diagrams, using the relationships proposed in the CNR-DT 204 (2006), were computed by varying some parameters like fiber geometrical properties and contents. The aim was to provide interaction diagrams which can be useful to design/check the strength of the concrete members reinforced with fibers and traditional steel reinforcement. Keywords: Experimental investigation; Fiber reinforced concrete; Post-peak behaviour; Eccentric loads; Stress-strain relationships.
Dottorato di Ricerca in Ingegneria dei Materiali e delle Strutture, Ciclo XX SSD, a.a. 2007
Keywords: Meccanica applicata; Scienza delle costruzioni; Materiali compositi; Calcestruzzi; Cemento armato